Development of VR-Based Islamic Education Learning Media for Hajj Pilgrimage Material in Islamic Senior High School - Tsaaniyatush Shoolihah Fauzan (Mazidah: Journal Of Educational Research, 2025)
This study aims to develop Virtual Reality-based Islamic Education learning media for hajj pilgrimage material in Islamic Senior High School (Madrasah Aliyah). Learning about hajj pilgrimage, which is abstract in nature and requires concrete visualization, poses particular challenges for Islamic Education teachers. This research employs the Research and Development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 60 12th-grade students from Islamic Senior High School. Data collection instruments included expert validation sheets, student response questionnaires, and learning achievement tests. The results show that the developed VR media received very feasible validation from material experts (4.5/5.0) and media experts (4.6/5.0). Student responses to the media reached 89% in the very positive category. There was a 35% increase in student learning outcomes compared to conventional learning. VR media proved effective in enhancing students' understanding of hajj pilgrimage procedures and providing an immersive learning experience.